PSYCHOLOGICAL CRITERIA OF TALENT IN RAISING A PERFECT PERSON (International Educators Conference, 2025)
In this article, the main attention of the leadership of our state is focused on the upbringing of the younger generation. The main reason for this is that the present and future of our great state and people are in the hands of our reliable youth. The greatness of our people is undoubtedly due to the health of its genetic resources and spiritual maturity. Even in the 21st century, worthy followers of our unique compatriots such as Ibn Sina, Al-Beruni, Al-Khwarizmi, and Imam Bukhari have emerged from among our youth.